Use of a modified drying medium to prevent discolouration of radiata pine sapwood during kiln drying - Pang, S.; Li, J. (Maderas. Ciencia y Tecnología, 2014)
Wood darkening and kiln brown stain (KBS) in kiln drying has caused significant economic loss to the wood processing industry which. Although extensive studies have been performed, feasible drying techniques have not yet been developed to economically produce bright, pale colour wood from commercial drying. The current work research has been conducted to dry radiata pine sapwood in hot air and in modified oxygen-free drying medium, namely, gases A, B and C. Four sets of matched samples were dried at three different temperatures of 50, 70 and 90ºC, one set in a tunnel dryer simulating commercial hot air drying and three sets in a newly designed stainless steel cylinder, which was placed in an oven, for tests using the three oxygen-free drying media. The results show that no obvious KBS was detected near the surface of sample boards dried in all of the oxygen-free gases except for one run using gas B at 70ºC. However, for hot air drying, the discolouration of wood could only be reduced by drying at the low temperature of 50ºC. How kiln drying in air at or above 70ºC induces surface darkening and KBS. These results indicate that using an alternative non-oxygen atmosphere to kiln dry wood could reduce surface discolouration and KBS.